Employees with mental illness - Possibilities and barriers in professional activity - Anna Cybula-Fujiwara; Dorota Merecz-Kot; Jolanta Walusiak-Skorupa; Andrzej Marcinkiewicz; Marta Wiszniewska (Nofer Institute of Occupational Medicine, 2015)
In Poland patients with psychiatric problems form a large group; in 2010 there were almost 1.5 million people for whom outpatient psychiatric care was provided, whereas approximately 200 thousand ill individuals were treated in 24-h psychiatric wards. Only 17% of the mentally disabled are professionally active. The results of many researches show that despite the detrimental influence of mental disorders on the employment (e.g., lower productivity, absenteeism, presenteism, increased risk of accidents at the workplace), professional activity can play a key role in the stabilization of the mental state, it can also help in disease recovery. People with mental disorders are a social group that is at the higher risk of exclusion from the job market. The opinion prevailing among employers is that mentally ill individuals have decreased ability to conduct professional activity, and social attitudes towards them tend to be based on marking and stigmatizing. This review tackles the advantages of working during the illness, barriers which people with mental disorders face on the job market when they want to either start or continue work, and professional functioning of people with diagnosed depression (e.g., affective disorders) and schizophrenia (representing psychotic disorders). The analysis of existing data show that to improve the situation of mentally ill people present on the job market close cooperation between the representatives of various medical specializations is necessary, as well as their active participation in the process of social and professional rehabilitation of people affected by mental disorders. Med Pr 2015;66(1):57-69